THE EFFECT OF FINANCIAL CONTENTS ON SOCIAL MEDIA TOWARDS FINANCIAL LITERACY ON GENERATION Z IN JAVA AND SUMATRA - Enya Angelica, Agnes
The number of internet users in Indonesia is increasing from year to year, and the most accessed platform in the internet is social media. The increase in social media users has grown the initiative of some social media users to share their knowledge to the other users, including financial contents. Especially, the pandemic made people search for financial advice and information more from the public sources compared to the pre-pandemic condition. The process of viewing financial contents in social media itself can be categorized as a type of financial education, the series of activities to increase financial literacy. The financial literacy index in Indonesia has shown improvements in the last few years. Despite the increase in the financial literacy index in Indonesia, the index is still low compared to other countries. The gap between financial literacy and financial inclusion also still exists. Since Generation Z has the highest internet penetration rate and spent the most time on the internet compared to other generations, financial contents in social media can be utilized to increase financial literacy in Generation Z, considering that Generation Z took the highest proportion compared to other generations. The objectives of this research are to find out the effect of financial literacy in Generation Z, the most significant factor of financial contents that affect financial literacy, and to find out which social media platform and type of content is the most impactful. The financial content on social media is measured by number of social media and content type, number of creators and topics watched, and duration, while financial literacy is measured by financial attitude, behavior, and knowledge. This research uses quantitative methods and the data is collected using an online questionnaire. This research gathered 287 samples from Java and Sumatra, and 222 of them are financial content viewers which are used in the data analysis. The multi linear regression result found that financial contents affect financial literacy for 20.4%. Respectively, the variable which has a positive significant effect is the number of financial topics watched which is the most significant factor, while the number of social media used to watch financial contents have negative significant effect. The ANOVA result found that people who are most frequently using YouTube to watch financial content have the highest financial literacy score average. The findings can be the considerations for the financial content creator itself, Generation Z, and institutions who have interests in financial literacy.